Internet of Things Architecture: Recent Advances, Taxonomy, Requirements, and Open Challenges - Yaqoob, Ibrar; Ahmed, Ejaz; Hashem, Ibrahim Abaker Targio; Ahmed, Abdelmuttlib Ibrahim Abdalla; Gani, Abdullah; Imran, Muhammad; Guizani, Mohsen (Institute of Electrical and Electronics Engineers, 2017)
Recent years have witnessed tremendous growth in the number of smart devices, wireless technologies, and sensors. In the foreseeable future, it is expected that trillions of devices will be connected to the Internet. Thus, to accommodate such a voluminous number of devices, scalable, flexible, interoperable, energy-efficient, and secure network architectures are required. This article aims to explore IoT architectures. In this context, first, we investigate, highlight, and report premier research advances made in IoT architecture recently. Then we categorize and classify IoT architectures and devise a taxonomy based on important parameters such as applications, enabling technologies, business objectives, architectural requirements, network topologies, and IoT platform architecture types. We identify and outline the key requirements for future IoT architecture. A few prominent case studies on IoT are discovered and presented. Finally, we enumerate and outline future research challenges.